Micropollutant removal by advanced oxidation of microfiltered secondary effluent for water reuse - James, Christopher P.; Germain, Eve; Judd, Simon J. (Elsevier Science B.V., Amsterdam., 2014)
The removal of micropollutants (MPs) from secondary municipal wastewater by an advanced oxidation process (AOP) based on UV irradiation combined with hydrogen peroxide (UV/H2O2) has been assessed through pilot-scale experiments incorporating microfiltration (MF) and reverse osmosis (RO). Initial tests employed low concentrations of a range of key emerging contaminants of concern, subsequently focusing on the highly recalcitrant compound metaldehyde (MA), and the water quality varied by blending MF and RO permeate. Under optimum H2O2 and lamp power conditions, AOP achieved significant removal (>99%) of N-nitrosodimethylamine (NDMA) and endocrine disrupting compounds (EDCs) for all waters. Pesticide removal, in particular metaldehyde, atrazine and 2,4,5-trichlorophenoxyacetic acid, was dependent on water transmittance (UVT), and levels of TOC and other hydroxyl radical (OH) scavengers. Further analysis of MA removal showed UVT, hydraulic retention time and H2O2 dose to be influential parameters in determining degradation as a function of UV dose. A cost assessment revealed energy consumption to account for 65% of operating expenditure with lamp replacement contributing 25%. A comparison of three unit process sequences, based on MF, RO, AOP and activated carbon (AC), revealed MF-RO-AOP to be the most cost effective provided management of the RO concentrate stream incurred no significant cost. Results demonstrated AOPs to satisfactorily reduce levels of the more challenging recalcitrant MPs to meet stringent water quality standards for wastewater reuse, but that practical limitations exist and the cost penalty is significant.